SDG-Oriented Compulsory Courses in Higher Education: An Exploratory Case from Turkey - Gover, Ibrahim Hakan; Ayten, Asim Mustafa (Emerald Group Publishing Ltd, 2026)
Purpose This study aims to examine students' perceptions of a set of compulsory Sustainable Development Goal (SDG)-oriented courses implemented across undergraduate programmes at a newly-established Turkish state university. Rather than evaluating individual courses, the study explores how a compulsory, SDG-framed curricular approach is associated with students' reported sustainability awareness, civic orientation and social engagement within a specific institutional context.Design/methodology/approach Data were collected from 325 undergraduate students enrolled in four compulsory SDG-oriented courses during the 2024-2025 academic year using a non-probability convenience sampling approach. A 19-item structured survey was administered to capture students' self-reported awareness and attitudes related to sustainability and social responsibility. Descriptive and inferential analyses (including t-tests and ANOVA after verifying normality assumptions) were conducted using SPSS and R.Findings The findings, derived from a composite impact scale, suggest that participation in SDG-oriented compulsory courses is associated with higher levels of sustainability awareness and positive orientations towards civic responsibility and social engagement. Differences were observed across demographic groups, with female students and those reporting prior familiarity with sustainability concepts indicating stronger perceived impacts. Given the exploratory design and reliance on self-reported data, the results should be interpreted as indicative rather than conclusive.Research limitations/implications The study is limited by its cross-sectional design, convenience sampling and reliance on self-reported perceptual data, which restricts causal interpretation and generalisability. The findings capture the initial, formative stages of learning rather than long-term transformation. As the data were collected from students enrolled in the earlier and intermediate stages of a set of compulsory SDG-based courses, the findings do not capture longer-term educational effects associated with the full curricular sequence. Future research employing longitudinal and comparative designs could provide deeper insight into how SDG-oriented curricular approaches develop over time and across institutional contexts.Practical implications The study provides empirical insight into how compulsory, SDG-oriented courses may contribute to students' sustainability-related awareness and civic orientations within higher education curricula. For curriculum developers and policymakers, the findings highlight both the potential and the limitations of using dedicated courses as one possible approach to embedding education for sustainable development.Social implications By foregrounding students' perspectives, the study contributes to ongoing discussions on the role of higher education in supporting sustainability-oriented values and social responsibility.Originality/value This study contributes exploratory, context-specific evidence on students' perceptions of SDG-oriented compulsory courses in Turkish higher education, offering a cautious empirical basis for further discussion and research on education for sustainable development at the institutional level.
Keywords: Societal Benefit; Turkey; Sustainable Development Goals; Third Mission; Higher Education; Sustainability; Mandatory Courses; Community Engagement